2011
DOI: 10.1021/jf201950y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Natural and Polyphenol-free Apple Pomace and the Effect of This Dietary Ingredient on Intestinal Fermentation and Serum Lipid Parameters in Rats

Abstract: Unprocessed pomace containing 61% of dietary fiber (DF) and 0.23% of polyphenols (PP) and ethanol- or ethanol/acetone-extracted pomaces containing 66% DF and 0.10% PP and 67% DF and 0.01% PP, respectively, were subjected to a 4 week study in rats. The aim of the study was assessing the advantages of dietary supplementation with the above pomaces. To measure the animal response to dietary treatments, parameters describing cecal fermentation and lipoprotein profile were assessed. The dietary use of 5% unprocesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 58 publications
3
43
5
Order By: Relevance
“…The present experiment demonstrated the beneficial influence of dietary quarks on fermentative processes in the hind gut, as characterised by the acidification of the caecal digesta (Kosmala, Kolodziejczyk, Zdunczyk, Juskiewicz, & Boros, 2011). This pH decline could be explained by significantly lower concentrations of caecal ammonia in the S and T groups.…”
Section: Discussionsupporting
confidence: 55%
“…The present experiment demonstrated the beneficial influence of dietary quarks on fermentative processes in the hind gut, as characterised by the acidification of the caecal digesta (Kosmala, Kolodziejczyk, Zdunczyk, Juskiewicz, & Boros, 2011). This pH decline could be explained by significantly lower concentrations of caecal ammonia in the S and T groups.…”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that increased dietary polyphenol content reduces the enzymatic activity of large gut microbiota (Kosmala et al, 2011). An earlier study of HT and LT FB seeds added to rat diets (Zduńczyk et al, 2003) revealed no significant differences in the activities of α-glucosidase, β-glucosidase, α-galactosidase and β-galactosidase, but LT seeds significantly increased the activity of microbial β-glucuronidase.…”
Section: Discussionmentioning
confidence: 99%
“…The proanthocyanidin content of fruit pomaces was determined in a separate procedure described by Kennedy and Jones [24]. The polyphenol compositional analysis was described in detail in another study [25]. …”
Section: Methodsmentioning
confidence: 99%